A new genus of the tribe Parahiraciini (Hemiptera: Fulgoromorpha: Issidae) from China with the description of two new species - Zhang, Zheng-Guang; Chen, Xiang-Sheng (Zootaxa, 2012)
A new issid genus of the tribe Parahiraciini (Hemiptera: Fulgoromorpha: Issidae) is described from China: Neotetricodesgen. nov.. Two new species, N. quadrilamina sp. nov. (China: Guizhou, Leigongshan National Natural Reserve) and N.kuankuoshuiensis sp. nov. (China: Guizhou, Kuankuoshui National Natural Reserve), are described and illustrated. Thetribe Parahiraciini is discussed briefly. A key to the genera in the tribe Parahiraciini and a key to species of the genus Neotetricodes are given.